1987
DOI: 10.1073/pnas.84.2.575
|View full text |Cite
|
Sign up to set email alerts
|

Unusual cardioactive peptide (CCAP) from pericardial organs of the shore crab Carcinus maenas

Abstract: Unusual cardioactive peptide (CCAP) from pericardial organs of the shore crab Carcinus maenas (crustacean ABSTRACT An unusual crustacean cardioactive peptide (CCAP) from the pericardial organs of the shore crab Carcinus maenas has been purified to homogeneity by a two-step reversed-phase HPLC procedure. Manual microsequencing using the 4-(NN-dimethylamino)azobenzene 4'-isothiocyanate/ phenylisothiocyanate double-coupling technique and automated gas-phase sequencing of the oxidized peptide revealed that CCAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
1
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(103 citation statements)
references
References 18 publications
(24 reference statements)
2
95
1
4
Order By: Relevance
“…CCAP was initially identified by its cardioacceleratory action on the heart of the shore crab (47) and in the tobacco hawkmoth, Manduca (8). The primary structure of this peptide appears to be strictly conserved across the arthropods (47,48).…”
Section: Drosophila Gpcrs In the Nmur Group Are Activated By Prxa Pepmentioning
confidence: 99%
See 1 more Smart Citation
“…CCAP was initially identified by its cardioacceleratory action on the heart of the shore crab (47) and in the tobacco hawkmoth, Manduca (8). The primary structure of this peptide appears to be strictly conserved across the arthropods (47,48).…”
Section: Drosophila Gpcrs In the Nmur Group Are Activated By Prxa Pepmentioning
confidence: 99%
“…CCAP was initially identified by its cardioacceleratory action on the heart of the shore crab (47) and in the tobacco hawkmoth, Manduca (8). The primary structure of this peptide appears to be strictly conserved across the arthropods (47,48). Additional functions of CCAP include myotropic actions (25,49), induction of AKH release in corpora cardiaca of locust (50), and induction of ecdysis behaviors (51,52).…”
Section: Drosophila Gpcrs In the Nmur Group Are Activated By Prxa Pepmentioning
confidence: 99%
“…CCAP is a neuropeptide that was initially discovered in the shore crab Carcinus maenas for its ability to raise the heart rate [51]. CCAP is highly conserved within the arthropod phylum, being identical in most species [52].…”
Section: Crustacean Cardioactive Peptides -Corazoninecdysis Triggerinmentioning
confidence: 99%
“…CCAP was first purified and sequenced from the crab Carcinus maenas (Stangier et al, 1987), and has since been found in a large number of arthropod species (Stangier et al, 1989;Cheung et al, 1992;Furuya et al, 1993;Lehman et al, 1993;Dircksen, 1994).…”
Section: Abstract: Pyloric Rhythm; Crustacean Neuropeptide; Central mentioning
confidence: 99%